2020
DOI: 10.13057/biodiv/d211020
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compounds contained in young and mature leaves of agarwood species Wikstroemia tenuiramis and its antioxidant properties

Abstract: Abstract. Batubara R, Hanum TI, Affandi O, Wahyuni HS. 2020. Chemical compounds contained in young and mature leaves of agarwood species Wikstroemia tenuiramis and its antioxidant properties. Biodiversitas 21: 4616-4622. The genus Wikstroemia is one of the genus of agarwood producing trees which has not been widely researched and published. One type of this genus is Wikstroemia tenuiramis Miq, which grows naturally in North Sumatra, the leaves are like other types of agarwood leaves can be used as raw material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results of previous studies that the antioxidant of agarwood leaf type W. tenuiramis and cultivated agarwood leaf type A. mallacensis had IC50 values of 30,482 and 41,130 μg/ml, in this study, ethanol extract was tested [12]. The antioxidant activity of agarwood leaf, fresh leaves and rotting leaves of type W. tenuiramis Miq was 27,78 and 28,80; 25,35 and 28,59 g/m, respectively, in ethanol solvent and hot water [1], in this study, the viscous extract, both ethanol extract and hot water extract, were tested.…”
Section: Antioxidant Of Hot Water Extract Of Agarwood Leaf Type W Ten...mentioning
confidence: 93%
See 1 more Smart Citation
“…The results of previous studies that the antioxidant of agarwood leaf type W. tenuiramis and cultivated agarwood leaf type A. mallacensis had IC50 values of 30,482 and 41,130 μg/ml, in this study, ethanol extract was tested [12]. The antioxidant activity of agarwood leaf, fresh leaves and rotting leaves of type W. tenuiramis Miq was 27,78 and 28,80; 25,35 and 28,59 g/m, respectively, in ethanol solvent and hot water [1], in this study, the viscous extract, both ethanol extract and hot water extract, were tested.…”
Section: Antioxidant Of Hot Water Extract Of Agarwood Leaf Type W Ten...mentioning
confidence: 93%
“…A class of acid compounds includes 9-Octadecenoic acid (Z)-, methyl esters and hexadecanoic acid, methyl esters. The results of the Py GC-MS test revealed that a family of acidic compounds, specifically Octadecanoic acid (CAS) Stearic acid, was the predominant compound in both the old and young leaves of W. tenuiramis Miq [12]. The major ingredient with the highest concentration in agarwood leaves from Laru Village, type A. malaccensis Lamk, is octadecanoic acid (CAS) stearic acid [13].…”
Section: Identification Of Compounds By Gas Chromatography Mass Spect...mentioning
confidence: 99%